Respuesta :
Answer: 16
============================================
Explanation:
The full expanded expression is 4x^2-16x+16
Which you can get through these steps
(2x-4)^2
(2x-4)(2x-4)
y(2x-4) ...... let y = 2x-4
2xy - 4y
2x( y ) - 4( y )
2x( 2x-4) - 4( 2x-4 ) .... plug in y = 2x-4
4x^2 - 8x - 8x + 16
4x^2 - 16x + 16
The question is an illustration of expansion and factorization.
The last term of the expression is 16.
We have:
[tex](2x - 4)^2[/tex]
Expand
[tex](2x - 4)^2 = (2x - 4) \times (2x - 4)[/tex]
Further expand
[tex](2x - 4)^2 = 2x(2x - 4) - 4(2x - 4)[/tex]
Open brackets
[tex](2x - 4)^2 = 4x^2 - 8x - 48x + 16[/tex]
[tex](2x - 4)^2 = 4x^2 - 56x + 16[/tex]
Hence, the last term of the expression is 16.
Read more about expansion and factorization at:
https://brainly.com/question/8075902